1963
DOI: 10.1002/jlac.19636700116
|View full text |Cite
|
Sign up to set email alerts
|

2‐Desoxy‐Zucker, V. Digitoxigenin‐2‐desoxy‐β‐D‐allopyranosid

Abstract: 2-Desoxy-~-allose wird in ihr Tetra-p-nitro-benzoat iibergefiihrt, das unter der Einwirkung von HCI oder HBr das entsprechende krist. 2-Desoxy-3.4.6-tri-O-[p-nitro-benzoyll-a-D-ribo-hexosylhalogenid (111 a bzw. I11 b) ergibt. Das Bromid I11 b wird mit Digitoxigenin umgesetzt und liefert nach Verseifung das krist. Digitoxigenin-2-desoxy-~-~-allopyranosid (V), welches starke herzaktive Wirksamkeit besitzt.Mit dem Ziel, verwandte Hexoside von 3p. 14P-Dihydroxy-Sp-card-20(22)-enolid (Digitoxigenin, IV) zu syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1964
1964
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Much of the work in the ensuing decades focused on the use of deoxyglycoside bromides for the preparation of nucleoside analogues, , or thioglycosides . Two early reports describing the use (or attempted use) of 2-deoxyglycosyl halides in O -glycoside synthesis emerged in the early 1960s from Zorbach and co-workers during early synthetic studies on digitoxin. , Here the authors demonstrated that reacting 1-bromo-2-deoxy-3,4,6-tri- O - p -nitrobenzolyl ribopyranose 9 with digitoxigenin 10 , followed by removal of the p -nitrobenzoyl (PNB) protecting groups, afforded the desired digitoxin derivative 11 in 46% as a single β-anomer (Scheme ).…”
Section: Direct Synthesismentioning
confidence: 99%
“…Much of the work in the ensuing decades focused on the use of deoxyglycoside bromides for the preparation of nucleoside analogues, , or thioglycosides . Two early reports describing the use (or attempted use) of 2-deoxyglycosyl halides in O -glycoside synthesis emerged in the early 1960s from Zorbach and co-workers during early synthetic studies on digitoxin. , Here the authors demonstrated that reacting 1-bromo-2-deoxy-3,4,6-tri- O - p -nitrobenzolyl ribopyranose 9 with digitoxigenin 10 , followed by removal of the p -nitrobenzoyl (PNB) protecting groups, afforded the desired digitoxin derivative 11 in 46% as a single β-anomer (Scheme ).…”
Section: Direct Synthesismentioning
confidence: 99%
“…4-Amino-l-(2-deoxy-6-0 -phosphono-/?-D-,rjfeo -hexopyranosyl)-2-pyrimidinone, Ammonium Form (29). 4-Amino-1-(2-deoxy-d-D-nbo-hexopyranosyl)-2-pyrimidinone (13) was treated in the same manner as described for the synthesis the AMP analogue 27, but the reaction was terminated after 2.5 h and the overall yield of 29 was 83%: 4H NMR (Me2SO-d6) 7.58 (d, 1, CgH, J = 7.18 Hz), 7.26 (s, 2, NH2, exchanged with D20), 5.99 (m, 1, CVH), 5.84 (d, 1, C5H, J = 7.18 Hz), and other sugar protons; 31P NMR (D20, pH 11.0) 6.73 (s).…”
Section: Methodsmentioning
confidence: 99%
“…Cl' 7887 (2) 1511 (3) 7134 ( 5) 26 (1) C2' 7650 (3) 583 (3) 5941 ( 5) 32 (1) C3' 6611 (2) 375 (3) 5734 ( 5) 29 standard deviation values are in parentheses. 6 Hydrogen atoms for which parameters were calculated are omitted.…”
Section: Conformation and Anomeric Configurationmentioning
confidence: 99%
“…spectrum showed resonances at y 4.13 (C-l doublet, J = 3.5 c.p.s. ), 6.11 (benzylthio singlet), 6.45 (C-6, 2 proton quartet), 6.85 (C-5, one proton multiplet), 8.58 and 8.73 (isopropylidene methyls). Anal.…”
mentioning
confidence: 99%
“…30-60°), affording 0.065 g. of crystals, m.p. 165-166°; [a]24 + 54.5°( 1%); JC»1 2.99, 3.02 and 6.42 (NH), and 5.68 (O-acetyl C=0), 6.02 µ (amide C=0); there was no appreciable absorption near 5.90 µ, suggestive of an S-acetyl carbonyl, nor near 7.40 µ, suggestive of the methyl group of the S-acetate. The n.m.r.…”
mentioning
confidence: 99%